Potential scaling strategies for Farmer FIRST Project - Singh, A K; Chahal, V P; Kumar, Shiv; Jhajhria, Abimanyu; Amit, Amit; Abdulla, Abdulla (Indian Farming, 2022)
Replication and diffusion strategies only contribute to systemic change when used in conjunction with a variety of other strategies that ensure impacts are scaled up or deep. Interestingly, the three types of scaling and their strategies can interact in powerful ways to advance systemic change goals. Dimensions of large-scale change efforts are: the quantifiable breadth of people and systems included; the institutional shifts in law, policy and resource flows that are necessary; and the subjective and inter-subjective transformations in values, relationships and agrarian-cultural practices that support durable system-wide change. Furthermore, by tracing the patterns of scaling, it is a combination of scaling out, up, and deep that is most likely to lead to large systems change, rather than any single strategy. An FFP can not simply expect to scale up to effect systems change without having gone through the lessons and capacity building experiences that occur when scaling out, or scaling deep in real-life situation. Additionally, as scaling occurs, it is essential to ensure that the endurance and stamina of leadership can persist for the duration of time that is required for scaling an initiative. The question that remains for the future is, how much of this can be ‘taught’, so that non-profits and funders today can leapfrog on the scaling successes of the past.